Nursing Care In A Pregnant Adolescent With Urinary Tract Infection In A Barranquilla Clinic 2019-1 - Lastre Amell Gloria; Montenegro Rivera Carelys; Carmen Carrero González; Indiana Rojas Torres; Diana Rodríguez Villa; Jorge Rodríguez López; Maria Alejandra Orostegui; Mariela Suarez Villa; Yulis Adarraga Escorcia; Geraldine Blanco Marimon; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
The Nursing Care Process, defined as a systemic, organized, logical and sequential method, which allows providing effective, timely and precise interventions, which favor the satisfactory evolution of patients inside and outside health institutions Objective: Provide nursing care A pregnant adolescent with impaired urinary elimination in a level II clinic in Barranquilla 2019-1. Methodology: clinical case report of a 15-year-old pregnant woman who applied the nursing process from the point of view of Betty Neuman’s theory with the support of family health instruments. Results: The primary nursing diagnosis was impaired urinary impairment R/C urinary tract infection, identifying it according to a scale of 1. Seriously compromised evidenced by frequent urination and urinary incontinence; having intervened on the patient according to her complaints, it went to a scale of 3. Moderately compromised. The other nursing diagnosis was ineffective protection, related to ineffective health self-management, evidenced by lack of knowledge about urinary infection and 15-year-old first-time pregnant, indicating a scale of 1. Seriously compromised, where the patient underwent a change of style of life to reduce the risk, passed to a scale of 4. Slightly compromised, evidencing improvement in his state of health. Conclusions: Care from the nursing care process favors quality care and with a comprehensive view of the subject, benefiting the patient’s evolution.